Material didáctico y su aporte en el desarrollo cognitivo en los niños de inicial, del subnivel dos de la Unidad Educativa Francisco Huerta Rendón cantón Babahoyo - Barros Soto, Leydi Roxana (2022)
This case study research work shows the importance of didactic material and its contribution to the cognitive development of children, which was carried out in the "Francisco Huerta Rendon Educational Unit", in order to publicize the benefits, uses and contributions of using didactic resources as a source of support for the intellectual development of students and achieving significant learning, the relevant research was based on the UTB Research Line: Education and social development and with the Line of career research: motivation and self-regulation in educational contexts, it is also mentioned what Jean Piaget's theories are, which are in the contextual framework and the techniques to obtain the data handled were surveys, interviews and tabulations to know the results and to finish this what is the conclusion and the recommendations where the conclusion highlights that the teacher must know his students in order to achieve that his didactics work, leading to the knowledge that he wants each student to learn and to develop knowledge appropriate to his needs and concludes with the evidence attached which are photographs, tabulations and consistency matrix.